Pembinaan Warga Binaan Pemasyarakatan Wanita Di Lembaga Pemasyarakatan Klas II A Samarinda - Ony Rosifany, S.H., M.Hum (Prodi Ilmu Administrasi Negara, 2016)
Guidance of the accused is the material course or the effective andefficient received by the makes the change of their personality towardsthe better in thinkin, action or behaviour. This activity has been carriedout there well. The accused and involeved women given not only phisicsbut also mentality though there are any handicaps in the implementationsuch as the handicaps of infrastructure, tls, willing and want of thewomen themselves it is, therefore, difficut to get the best result towardsthe effective and efficient, useful as well.